PENGARUH PEMASARAN DIGITAL, INOVASI PRODUK DAN KUALITAS PRODUK TERHADAP PENINGKATAN PENJUALAN PRODUK UMKM DI MASA PANDEMI COVID-19 (STUDI KASUS PADA PELAKU UMKM DI KABUPATEN LAMPUNG BARAT) - Arianzah, Ahmad Taufik; Indriani, Wiewiek; Listyaningsih, Erna; Mufahamah, Euis; Harun, Harmani (Universitas Malahayati, 2023)
The influence of micro, small and medium enterprises on the economy of West Lampung Regency is very large but there are still problems that still need to be resolved. This quantitative research was conducted to determine the effect of digital marketing, product innovation and product quality partially and simultaneously on increasing product sales for micro, small and medium enterprises. The data collection technique in this study was through observation, distributing questionnaires to 40 respondents who are also small and mediumsized business actors assisted by the Small and Medium Enterprises Cooperatives, Industry and Trade Office of West Lampung Regency using google forms and literature studies. From the results of data analysis that has been carried out, it is obtained that digital marketing has an effect on increasing sales, product innovation has an effect on the variable of increasing sales, product quality has an effect on increasing sales and digital marketing variables, product innovation and product quality will have a simultaneous effect on the variable of increasing sales.